On the Notion of Fixability of PDDL+ Plans [Extended Abstract] - Percassi, Francesco; Scala, Enrico; Vallati, Mauro (Proceedings of the International Symposium on Combinatorial Search, 2023)
PDDL+ is an expressive formalism that allows for the use of planning in hybrid discrete-continuous domains. To cope with unexpected situations, it is crucial for deployed planning-based systems to efficiently repair existing plans. In this paper, we revisit a recently proposed FIXABILITY framework for expressing and solving problems from validation to rescheduling of actions in PDDL+ plans.